Multicultural challenges and redefining identity in East Asia - Kim, Nam-Kook (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2014)
Globalization and increased migration have brought both new opportunities and new tensions to traditional East Asian societies. 'Multicultural challenges and redefining identity in East Asia' draws together a wide range of distinguished local scholars to discuss multiculturalism and the changing nature of social identity in East Asia. Regional specialists review specific events and situations in China, Korea, Japan, Thailand, Vietnam, Singapore, Taiwan, Malaysia, Indonesia, and the Philippines to provide a focus on life as it is lived at the local level whilst also tracing macro discourses on the national issues affected by multiculturalism and identity. The contributors look at the uneven multicultural development across these different countries and how to bridge the gap between locality and universality. They examine how ethnic majorities and minorities can achieve individual rights, exert civic responsibility and explain how to construct a deliberative framework to make sustainable democracy possible. This book considers the emergence of a new cross national network designed to address multicultural challenges and imagines an East Asian community with shared values of individual dignity and multicultural diversity. With strong empirical support it puts forward a regulative ideal by which a new paradigm for multicultural coexistence and regional cooperation can be realized